Diagnostic Accuracy of Procalcitonin and C-reactive Protein for the Early Diagnosis of Intra-abdominal Infection After Elective Colorectal Surgery: A Meta-analysis. Issue 2 (August 2016) - Cousin, François; Ortega-Deballon, Pablo; Bourredjem, Abderrahmane; Doussot, Alexandre; Giaccaglia, Valentina; Fournel, Isabelle
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Intra-abdominal infections (IAIs) after elective colorectal surgery impact significantly the short- and long-term outcomes. In the era of fast-track surgery, they often come to light after discharge from hospital. Early diagnosis is therefore essential. C-reactive protein levels have proved to be accurate in this setting. Procalcitonin has been evaluated in several studies with conflicting results. This meta-analysis aimed to compare the predictive abilities of C-reactive protein and procalcitonin in the occurrence of IAIs after elective colorectal surgery. Methods: This meta-analysis included studies analyzing C-reactive protein and/or procalcitonin levels at postoperative days 2, 3, 4, and/or 5 as markers of intra-abdominal infection after elective colorectal surgery. Methodological quality was assessed by the QUADAS2 tool. The area under the curve summary receiver-operating characteristic was calculated for each day and each biomarker, using a random-effects model in cases of heterogeneity. Results: The meta-analysis included 11 studies (2692 patients). An IAI occurred in 8.9% of the patients. On postoperative day 3, area under the curve was 0.80 (95% CI, 0.76–0.85) for C-reactive protein and 0.78 (95% CI, 0.68–0.87) for procalcitonin. On postoperative day 5, their predictive accuracies were 0.87 (95% CI, 0.80–0.93) and 0.90 (95% CI, 0.82–0.98), respectively. The accuracy of C-reactive protein and procalcitonin did not differ at any postoperative day. Conclusions: Levels of inflammatory markers under the cutoff value between postoperative days 3 and 5 ensure safe early discharge after elective colorectal surgery. Procalcitonin seems not to have added value as compared to C-reactive protein in this setting.